Lockdowns are protecting China’s rural families from COVID-19, but the economic burden is heavy - Rozelle, Scott; Rahimi, Heather; Wang, Huan; Dill, Eve (International Food Policy Research Institute, 2020)
In response to the COVID-19 outbreak in December 2019, China implemented a nationwide travel blockade and quarantine policy that required all public spaces, businesses, and schools to shut their doors until further notice and placed restrictions on individuals leaving their homes or traveling. The lockdown was also implemented across China’s vast rural areas, home to more than 700 million people. These quarantine measures started during the annual Spring Festival in mid-January, when most rural residents had returned to their family homes to celebrate the Lunar New Year together. Many were migrant workers who had expected to return to China’s urban and industrial centers to continue working in factories, construction sites, and service sectors.